Five major outcomes of digitalization: relevance of a survival personality type during COVID-19 pandemic - Hamamoto, Yumi; Honda, Akio; Miura, Naoki; Tanabe-Ishibashi, Azumi; Oba, Kentaro; Ishibashi, Ryo; Sugiura, Motoaki (Frontiers in Psychology, 2023)
The COVID-19 pandemic required people to adapt rapidly to the digital transformation of society for social survival, which highlighted the divide between those who can and cannot digitalize. Previous studies investigated factors promoting adaptation to digitalization; however, outcomes from adaptation to a digitalized society have not been sorted into a parsimonious model, even though there should be several multifaceted outcomes (e.g., usefulness, economic profit, and social outcome), each of which is promoted by different factors. If the effects of individual background factors can be revealed, including the technical-environment and survival-relevant personality in relation to each outcome, it would help in the creation of a society where more people play an active role by adapting to digitalization. This study aimed to construct such a model by identifying major outcomes gained in a digitalized society and investigating individual factors that contribute to the degree of gain of each of these outcomes. Five dimensions were identified by online surveys and factor analysis: Socialization (outcomes derived from new social connections created online), Space–time (freedom from time and space constraints), Economics (monetary outcome by using digital services), and Information (ease and amount of acquisition of information) were the positive outcomes, whereas Loneliness (feelings of not being able to keep up with digitization) was identified as a negative outcome. We determined that technical-environmental factors (e.g., familiarity with digital techniques and the amount of money that can be used for digitalization) facilitated gain in four positive outcomes. Notably, leadership and conscientiousness facilitated the Socialization gain while etiquette suppressed it. These factors’ effects would reflect the importance of a personality trait prioritizing construction and maintenance of social relationships. This study implies that material outcomes (i.e., Space–time, Economics, and Information) are promoted by technical-environmental support, whereas social outcomes may additionally require motivation and a positive attitude for purposeful social engagement.